“Hope isn’t actually lost yet”: A reflexive thematic analysis exploring young people’s views and feelings towards climate change - Payton, Joanna (2023)
The psychological wellbeing impacts of climate change awareness are becoming increasingly recognised (Baker et al., 2021; Lawrance et al., 2021). Climate change has recently been highlighted as a significant issue and source of distress for children and young people (Hickman et al., 2021; Martin et al., 2022; Vergunst & Berry, 2022). However, the emerging evidence base is narrow and largely comprised of survey data. Rich and detailed accounts of children and young people’s responses to climate change (Ojala et al., 2021) and their views regarding related support are limited (Baker et al., 2021; Martin et al., 2022). Therefore, this study sought to answer two research questions: ‘what are the views, feelings, and experiences of young people concerned about climate change?’ and ‘what do young people perceive as helpful and unhelpful in supporting their climate change concerns?’